A cross-sectional study of swine influenza in intensive and extensive farms in the northeastern region of the state of São Paulo, Brazil - Almeida, Henrique Meiroz de Souza [UNESP]; Storino, Gabriel Yuri [UNESP]; Pereira, Daniele Araújo [UNESP]; Gatto, Igor Renan Honorato [UNESP]; Mathias, Luis Antonio [UNESP]; Montassier, Hélio José [UNESP]; de Oliveira, Luís Guilherme [UNESP] (Springer Nature, 2017)
Swine influenza (SI) is a seasonal infectious disease highly important to the world pig industry. Loss of daily weight gain, increased costs for the prevention and treatment of secondary infections are the main economic losses associated with the presence of this disease. However, some epidemiological features of SI remain quite unclear. This study focused on assessing the prevalence of swine influenza virus (SIV) infection in intensive and extensive pig herds and associating risk factors. A set of 601 blood samples of five intensive farrow-to-finish farms and 361 blood samples from 56 extensive farms were analyzed using an indirect ELISA kit CIVTEST SUIS INFLUENZA®, Hipra (Amer, Spain), in order to detect anti-SIV antibodies. In total, 24.13 % of samples from intensive herds were positive, while no positive samples were detected in extensive rearing herds. Sow and weaning piglets had the highest prevalence values. In the intensive rearing system, occurrence of reproductive disorders and exposure to recently introduced animals were positively associated with the disease occurrence in swine herds. The findings highlight the importance of sows in the epidemiology of the disease and bring information about risk factors involved in the occurrence of swine influenza in intensive herds.
Keywords: ELISA; Epidemiology; Orthmyxoviridae; Pigs; Porcine respiratory disease complex; SIV